Slovenska etnomuzikologija med preteklostjo in sedanjostjo - Omerzel, Mira (Traditiones (Ljubljana), 1999)
In her article the author analyzes the work of Dr. Zmaga Kumer and describes new aspects of the research of terminology and the development of "preclassical" folk instruments
Keywords: folk music; ljudska glasba; ljudska glasbila; Slovenia; Slovenija; terminologija; terminology; etnomuzikologija